Literature Review on the Biological Effects of Taraxacum Officinale Plant In Therapy - Faria, TC; Nascimento, C. C. H. C.; Vasconcelos, S. D. D. De; Stephens, P. R. S. (Asian Journal of Pharmaceutical Research and Development, 2019)
Since human beings have sought in nature, components that can obtain help in therapeutics or even in the cure of diseases. The progress made in the area of ​​science promoted the development of recognized and effective herbal medicines, as well as the search for the population, for less aggressive treatments. The evaluation of the antioxidant activity of plants has been an important issue taking into account its importance on human health, since the natural antioxidants present a reduced health risk, when compared to the synthetic ones that present toxic effect. From the Asteraceae family, of which the plant species Taraxacum officinale, popularly known as dandelion, stands out among the 71 species on the list of the Ministry of Health (RENISUS), scientifically affirmed, to treat liver disorders, inflammations, potential in the anti-bacterial, cytotoxic, antiviral, antiparasitic, antifungal activity, besides studies to verify its anticancer action and of carcinogenic prevention. The acute toxicity of Taraxacum officinale appears to be low, with LD50 values ​​estimated at 36.8g / kg and 28.8g / kg, for the whole plant. The adverse or complex toxic effects for T. officinale have not yet been reported. This review of the literature was elaborated through studies of articles contained in the Scielo, Google Scholar and Pub Med platforms. Through this review the importance of phytotherapy studies for pharmacological purposes was verified, aiming to improve the therapeutics.